2012
DOI: 10.4103/0970-1591.102696
|View full text |Cite
|
Sign up to set email alerts
|

Dedicated robotics team reduces pre-surgical preparation time

Abstract: Context:Robot-Assisted Laparoscopic Radical Prostatectomy (RALRP) requires significant preoperative setup time for the room, staff, and surgical platform. The utilization of a dedicated robotics operating room (OR) staff may facilitate efficiency and decrease costs.Aims:We sought to determine the degree to which preoperative time decreased as experience was gained.Materials and Methods:A total of 476 patients with a mean age of 60.2 years were evaluated (11/2006 to 1/2010). Data was assimilated through an inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…16,17 The utilization of a dedicated RS team has been associated with decreased preoperative setup times, as well as overall length of surgery. 18 Lasser and colleagues 18 demonstrated that operating room staff consistency decreased overall operating room times in 10-case increments through enhanced efficiency prior to the incision. The longer operating times reported in these studies do not appear to be associated with worse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 The utilization of a dedicated RS team has been associated with decreased preoperative setup times, as well as overall length of surgery. 18 Lasser and colleagues 18 demonstrated that operating room staff consistency decreased overall operating room times in 10-case increments through enhanced efficiency prior to the incision. The longer operating times reported in these studies do not appear to be associated with worse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Utilization of a dedicated operating room team experienced in robotic set-up, as is the practice in our institution, is critical in maintaining equivalent OR room and turnover times [19]. Partnering with surgeons experienced with rPLND for other indications can also help minimize the learning curve.…”
Section: Discussionmentioning
confidence: 99%
“…4,6,7,12 This is possibly because of the inclusion of a docking procedure that is not required for laparoscopic surgery. However, the time from admission to docking is expected to decrease as the team's surgical experience increases, 16 and anesthesia time may thus decrease and become similar to that of laparoscopic surgery as the number of surgeries increases. Furthermore, this study covered the first 2 years since robot-assisted rectal cancer surgery became covered by insurance in Japan, when many facilities introduced robotassisted surgery simultaneously.…”
Section: Discussionmentioning
confidence: 99%